2003
DOI: 10.1103/physrevd.67.026008
|View full text |Cite
|
Sign up to set email alerts
|

BPS states of strings in 3-form flux

Abstract: We count the BPS states of strings in uniform 3-form fluxes, using supersymmetric quantum mechanics derived from the κ-symmetric action for D-branes. This problem is relevant to the stringy physics of warped compactifications. We work on a type IIB T 6 /Z 2 orientifold with imaginary selfdual, quantized, 3-form flux. Ignoring the orientifold projection, the number of short multiplets living on a single string is the square of the units of 3-form flux present on the torus; the orientifold removes roughly half o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Studies of Dp brane classical solutions in flat space can be found for example in [7] and more recently [8]. Different studies of the conditions to have supersymmetric Dp branes in some supersymmetric compactifications with Ramond-Ramond (RR) fluxes are in [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Dp brane classical solutions in flat space can be found for example in [7] and more recently [8]. Different studies of the conditions to have supersymmetric Dp branes in some supersymmetric compactifications with Ramond-Ramond (RR) fluxes are in [9,10,11].…”
Section: Introductionmentioning
confidence: 99%